Management of diet in gastrointestinal cancer. Issue 1 (29th May 2020) - Shaw, Clare
Abstract : Nutrition and gastrointestinal cancer are inextricably linked. The metabolic effects of cancer along with changes in dietary intake, the development of cancer cachexia and the presence of sarcopenia can influence changes in body composition. These have a negative impact on quality of life and tolerance to cancer treatment. Treatment for cancer presents some significant nutritional challenges as nutrition impact symptoms may develop, be exacerbated by treatment and may contribute to a worsening in nutritional status. Nutrition screening and assessment should be an integral part of holistic patient care. The provision of appropriate, evidence-based dietary advice should occur before, during and after cancer treatment. Appropriate and timely methods of nutritional support across the spectrum of gastrointestinal cancer are needed to ensure that people are adequately supported during courses of treatment that can span weeks and months. These can range from standard approaches of supplementing oral intake to complex interventions such as managing high output intestinal stomas. The gastrointestinal tract is particularly susceptible to impact from systemic anti-cancer treatments and radiotherapy. Gastrointestinal late effects of cancer treatment are now recognised to present particular challenges in terms of both medical and nutritional management. These late effects have a significant impact on the individual and their quality of life in addition to implications for the health service. Dietary intake following cancer treatment has an impact on quality of life and future research may demonstrate its influence on the risk of recurrence of gastrointestinal cancer.